Edukasi Kepada Masyarakat Kelompok Nelayan Tentang Digitalisasi Pemasaran Ikan Untuk Meningkatkan Pendapatan Kelompok Nelayan Desa Bajomulyo Kecamatan Juwana Pati - Adenanthera Lesmana Dewa; Agus Aji Samekto; Dhanan Abimanto (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Community service activities are one form of implementation of the Tri Dharma of Higher Education which aims to have a direct impact on improving the quality of life of the community. AMNI Maritime University conducted community service activities in Bajumulyo Village, Juwana District, Pati Regency, as a form of support for the coastal community economic empowerment program launched by the Pati Regency Government. This activity involved lecturers, students/cadets, and the local community in an active and collaborative manner. The enthusiasm of the Bajumulyo Village community in participating in various series of activities demonstrated the need and awareness of the importance of technological adaptation, especially in terms of digitalizing the marketing of fish catches. The main objective of this activity was to increase the income of fishing groups through the use of digital media as a means of promotion and distribution of marine products. The method of implementation of the activity was carried out through a participatory approach in the form of direct training and coaching, field observations, interviews with local fishermen, and literature studies to strengthen the conceptual framework and practices in the field. Training materials included digital marketing strategies, the use of e-commerce platforms, social media, and attractive fishery product packaging techniques. Indicators of the success of this program were an increase in fishermen's ability to use digital technology to market their products and an increase in the income of fishing families after participating in the program. Observations indicate that this training has had a positive impact on community understanding of the importance of digitalization in marketing fish catches.